2012
DOI: 10.1175/waf-d-11-00042.1
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Characteristics and Probability of Rapidly Intensifying Tropical Cyclones in the Western North Pacific Basin

Abstract: The China Meteorological Administration (CMA) and the National Centers for Environmental Prediction (NCEP) reanalysis datasets are employed to examine the large-scale characteristics of rapidly intensifying western North Pacific tropical cyclones (TCs). The results show that of all 27 581 samples for the period 1970–2007, 85%, 65%, and 47% of all tropical depressions (TDs), tropical storms (TSs), and typhoons (TYs), respectively, intensify. Of the 1214 TCs, 18%, 70%, 30%, and 10% of all tropical cyclones, supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
83
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 40 publications
16
83
1
Order By: Relevance
“…Ventham and Wang (2007) found that in the WNP, RI is characterized by lower-level monsoon confluence environmental flows, which play critical roles in determining RI. Shu et al (2012) examined the effects of large-scale environmental factors on TC RI in the WNP. It was found that the RI cases have higher lower-tropospheric relative humidity (RHUM), lower VWS, and more easterly uppertropospheric flow than the non-RI cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventham and Wang (2007) found that in the WNP, RI is characterized by lower-level monsoon confluence environmental flows, which play critical roles in determining RI. Shu et al (2012) examined the effects of large-scale environmental factors on TC RI in the WNP. It was found that the RI cases have higher lower-tropospheric relative humidity (RHUM), lower VWS, and more easterly uppertropospheric flow than the non-RI cases.…”
Section: Introductionmentioning
confidence: 99%
“…) per 24 h is employed to define RI events since it represents the nearly 95th percentile of the intensity changes in 24 h in the WNP (Wang and Zhou 2008;Shu et al 2012).…”
mentioning
confidence: 99%
“…Especially, rapid intensification (RI) is one of the most challenging and the least well understood problems in tropical cyclone prediction today. Furthermore, the most intense TCs in the Northern Hemisphere often have a RI period during the peak season, and account for nearly three-quarters of all the RI events (Frederick 2003;Kaplan and DeMaria 2003;Ventham and Wang 2007;Shu et al 2012). RI also poses a significant threat to ships and a growing number of coastal communities.…”
Section: Introductionmentioning
confidence: 99%
“…1). A recent study by Shu et al (2012) also showed that the intensifying events usually have more easterly upper-tropospheric flow than the nonintensifying events, suggesting a possible role of the WNPSH for the former. Since whether and how the WNPSH influences TC intensity has not been obtained, the potential impacts of environmental parameters associated with the WNPSH were not taken into account in developing MPI in Zeng et al (2007).…”
Section: Shoujuan Shu Et Al: Environmental Influences On the Intensimentioning
confidence: 92%